Peranan fungsi regulerend pajak air tanah terhadap konservasi sumber daya air - Mulyanti, Dewi; Farida, Ida; Nuriyah; Amalia, Emma; Setiadi, Yadi (Badan Kemitraan Inovasi dan Kewirausahaan Universitas Galuh, 2023)
The use of water is highly needed for human primary needs and industry. Thus, the government issued a policy related to the function of regulating groundwater taxes to regulate the use of groundwater to make it in harmony with the sustainability of the preservation of water resources. The regulatory function of groundwater tax is not optimal and tax collection plays a greater role in local government revenue, so it does not support the conservation function of water sources. Thus, this research is important for researchers to formulate ‘what is the role of the regular function of the groundwater tax that applies in Indonesia?’ and ‘what is the regulatory model which can synergize groundwater taxes with water resource conservation?’ This research uses several methods in data collection and compilation. The approach method used in this study is normative juridical under qualitative data analysis. The analytical descriptive method is employed to comprehensively describe and systematically examine primary and secondary data, which then analyzes the research object to provide a clear picture connected to relevant legal theories to find the government policy as the concept of thought. The research result showed that the function of the groundwater tax regulerend has not played a role in the conservation of water resources. The role of regular function of groundwater tax requires it to be used to control the sustainable use of groundwater for the greatest prosperity of the people, both now and in the future. Through